A long walk to freedom: Charting a way for doing comparative translation studies in Africa - Marais, Kobus (Stellenbosch Papers in Linguistics Plus, 2021)
In recognition of the work that Ilse Feinauer has done for the development of translation studies in Africa, this paper considers the position of translation studies on the continent. It proposes a comparative approach to translation studies on the continent to counter the two extremes of universalism and provincialism in the field of study. After considering some of the epistemological problems that translation studies faces in Africa, the paper suggests that a complex adaptive systems approach linked to a semiotic conceptualisation of translation allows for this kind of comparative approach. The paper concludes with some suggestions about the nature of comparative work in translation studies.